Communicating with Islamic Communication and Broadcasting English Language Learners: Berkomunikasi dengan Pembelajar Komunikasi dan Penyiaran Islami Bahasa Inggris - Masruuroh, Lina; Kusuma, Lyla Anggerwina (JEES (Journal of English Educators Society), 2018)
Proper Teacher Talk (TT) used in the EFL classroom contributes to the effective communication in TEFL. Teachers who are expected to implement proper and effective teacher talk are apparently seeing this as one of the most complicated elements to be appropriately integrated in EFL class due to the different context between target language and first language and also the excessive target language exposure that is given by English teacher to the students as one of authentic learning process in the classroom. Many research focus on researching effective TT strategy in general EFL classroom, however, there is ony limited number of them that focuses on researching this concept in Islamic classroom with its Islamic culture, Islamic learners and Islamic situations. This descriptive qualitative study discussed and proposed the effective teacher talks in supporting the success of teaching english as a foreign language classroom in Islamic context. This article had anaysed the interview result from 7 English-Islamic lecturers in Islamic Broadcasting and Communication Learners (KPI) major and used TT features which later focussed on its ammount, diction and questioning type under SLA theory. This article aims to explain why and what types of language of the proper communication style and strategies should be applied by the English lecturers in Islamic higher education for having the effective teacher talk to English-Islamic learners, specifically to Islamic Broadcasting and Communication Learners, that could contribute to a professional development in English Language Teaching.